Digital Financial Literacy, Financial Behaviors, and Well-Being: Evidence from Rural Millennial Families in Lumajang East Java - Khoirunisa, Rizqi; Mustofa, Ahmad; Setyawan, Bimo; Kurnia, Lely Indah; Purnomo, Subekhi Hadi (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2025)
Millennial families in rural areas play an important role in driving the digital economy but still face gaps in financial literacy and access to digital financial services. This study aims to analyse the effect of Digital Financial Literacy (DFL) on Financial Well-Being (FWB) through Spending Behavior, Saving Behavior, and Investment Behavior among millennial families in rural areas of Lumajang, East Java. The research employed a quantitative survey method involving 400 respondents selected using quota sampling and analyzed with PLS-SEM. The results indicate that DFL does not directly affect FWB but has an indirect effect through the mediating variables of spending, saving, and investment behaviors. These findings highlight the importance of enhancing digital financial literacy accompanied by positive changes in financial behavior to improve the financial well-being of millennial families in rural areas